Seed storage in polyethylene bags of a recalcitrant species (Quercus ilex): analysis of some bio-energetic and oxidative parameters (Acta Physiologiae Plantarum, 2012)
Some technological and physiological aspects were analysed during seed storage of holm oak (Quercus ilex L.), a typical Mediterranean recalcitrant species. Considering the mild dormancy and desiccation sensitivity of these seeds, the inﬂuence of the storage environment on viability was examined. Acorns were maintained at low temperature and at high moisture content either inside thin polyethylene bags or mixed with peat in a bin. Storage in polyethylene bags, if compared with peat treatment, maintained optimal seed quality parameters. The effects of the two treatments on some physiological parameters were analysed during 1-year seed storage. Acorns stored in a bin with peat started to germinate early and exhibited a more rapid seed deterioration caused by metabolism-linked oxidative damage. The latter phenomenon was linked to a higher respiration and H2O2 level, induction of catalase activity, as well as lowered glutathione pool and ATP content. In addition, a more oxidized redox poise was observed. On the contrary, the plastic ﬁlm of polyethylene, limiting gaseous exchanges, maintained acorn metabolic activity at low levels and allowed the accumulation of ethylene inside the storage atmosphere. These factors, inducing a dormant-like state, could have played a crucial role in prolonging seed storage.